Unpacking the Gestures of Chemistry Learners: What the Hands Tell Us About Correct and Incorrect Conceptions of Stereochemistry. Issue 3 (16th March 2021) - Ping, Raedy; Church, R. B.; Decatur, Mary-Anne; Larson, Samuel W.; Zinchenko, Elena; Goldin-Meadow, Susan
ABSTRACT: In this study, adults naïve to organic chemistry drew stereoisomers of molecules and explained their drawings. From these explanations, we identified nine strategies that participants expressed during those explanations. Five of the nine strategies referred to properties of the molecule that were explanatorily irrelevant to solving the problem; the remaining four referred to properties that were explanatorily relevant to the solution. For each problem, we tallied which of the nine strategies were expressed within the explanation for that problem and determined whether the strategy was expressed in speech only, gesture only, or in both speech and gesture within the explanation. After these explanations, all participants watched the experimenter deliver a 2-minute training module on stereoisomers. Following the training, participants repeated the drawing + explanation task on six new problems. The number of relevant strategies that participants expressed in speech (alone or with gesture) before training did not predict their post-training scores. However, the number of relevant strategies participants expressed in gesture only before training did predict their post-training scores. Conveying relevant information about stereoisomers uniquely in gesture prior to a brief training is thus a good index of who is most likely to learn from the training. We suggest that gesture reveals explanatorily relevant implicit knowledge that reflects (and perhaps even promotes) acquisition of new understanding.